JUVENILE MYOCLONIC EPILEPSY: A FOCUS ON THE EFFICACY OF THERAPY AND THE RATE OF RELAPSES ACCORDING TO LONG-TERM FOLLOW-UP DATA - K. Yu. Mukhin; N. V. Freidkova; L. Yu. Glukhova; O. A. Pylaeva; M. B. Mironov; N. E. Kvaskova (Русский журнал детской неврологии)
Juvenile myoclonic epilepsy (JME) is a type of adolescent-onset idiopathic generalized epilepsy with the appearance of massive myoclonic seizures and, in most cases, generalized convulsions occurring chiefly in the period after awakening. It is assumed that there is a two-locus (dominant and recessive) model of inheritance of JME; moreover, the dominant gene is located on the short arm of chromosome 6. JME is one of the most common types of epilepsy and most frequent among idiopathic generalized epilepsies. Its rate is 5 to 11 % of all types of epilepsy with some female predominance. The diagnosis of JME creates no problems in typical cases. The disease is generally manifested by a concurrence of myoclonic (usually in the hands) and generalized clonic-tonic-clonic seizures occurring during waking. Typical absences and epileptic myoclonus of the eyelid are rarer. Seizures are clearly provoked by sleep deprivation. As in other types of idiopathic epilepsy, the patients’ neurological status is normal; no intellectual disabilities are observed. This type of epilepsy is well treatable and, when initial monotherapy is correctly used, sustainable remission occurs immediately in the vast majority (75–85 %) of the patients with JME. However, the problem of these patients, unlike that of patients with many forms of idiopathic epilepsy, is that sleep pattern disturbance, missing a dose of antiepileptic drugs (AED), or therapy refusal give rise to relapse of seizures in the vast majority of patients even in long-term remission.Due to the fact that the data available in the literature on the efficacy of therapy in patients with JME and particularly on the results of its discontinuation are contradictory, the authors of the paper conducted an investigation to determine therapeutic effectiveness and the frequency of relapse of seizures in patients with JME during a long-term follow-up.The study enrolled 106 JME patients who had been regularly followed up at the Saint Luka’s Institute of Pediatric Neurology and Epilepsy for 3 to 28 years (mean 8.6 years). The authors detailed the clinical characteristics of the disease and the results of the investigation in the observed patients. The investigation showed that JME was the second common type (next to rolandic epilepsy) among all idiopathic epilepsies. Clinical remission lasting 3 years or longer was achieved in the vast majority of cases (89.6 %); however, clinical and electroencephalographic remission was in only 22 % of the patients. Treatment was not absolutely ineffective in any of the cases. Monotherapy for JME was used in most patients (79 %), duotherapy in 17 % and polytherapy (3 AEDs) in 4 %. Valproate was most commonly used as monotherapy for JME (56 %); levetiracetam and topiramate were more rarely in 13 and 8 %, respectively.Unfortunately, despite the high effect of treatment, the recurrence rate during or after discontinuation of AED therapy (which was gradually done under guidance of video-assisted electroencephalographic monitoring at least 3–4 years after remission) was very high (92 %). The recurrence risk was highest when the dose was reduced by more than 50 % and within the first year after therapy discontinuation. Multiple attempts to discontinue the treatment were made at an interval of an average of 4.3-years of remission in a number of patients. The authors identified a number of factors increasing the recurrence risk after withdrawal of an AED.